Cold water immersion of the hand and forearm during half-time improves intermittent exercise performance in the heat - Iwahashi, Manami; Chaen, Yudai; Yanaoka, Takuma; Kurokawa, Yasutsugu; Hasegawa, Hiroshi (Frontiers in Physiology, 2023)
To investigate the effect of cold water immersion of the hand and forearm during half-time (HT) on intermittent exercise performance and thermoregulation by imitating intermittent athletic games in the heat. In a randomised crossover design, 11 physically active men performed the first half (first and second block) and second half (third and fourth block) intermittent cycling exercise protocol, which consisted of a 5-s maximal power pedalling (body weight × 0.075 kp) every minute separated by 25-s of unloaded pedalling and rest (30 s) in the heat (33°C, 50% relative humidity). The two halves were separated by a 15-min HT. During HT, the participants were assigned to the CON (sedentary resting) or COOL (immersion of hands and forearms in cold water at 15-17°C) group. The mean power output in the second half was significantly greater (third and fourth block: p<0.05) in the COOL than in the CON group. Moreover, there was a significant decrease in the rectal (0.54±0.17℃, p<0.001) and mean skin (1.86±0.34℃, p<0.05) temperatures of the COOL group during HT. Furthermore, the heart rate (16±7bpm, p<0.05) and skin blood flow (40.2±10.5%, p<0.001) decreased at the end of HT in the COOL group. In the second half, thermal sensation was more comfortable in the COOL group (p<0.001). Cold water immersion of the hand and forearm during HT improved physiological and reduced perceived heat stress. Moreover, it prevented a reduction in intermittent exercise performance in the second half.